Personal data and medical research: conditions, inconsistencies, and legal perspectives based on the interpretative evolution of the Italian Data Protection Authority (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
The article, starting from an analysis of the most recent measures taken by the Italian Data Protection Authority on retrospective studies, highlights the ethical-legal, methodological, and operational issues related to the effort required from data controllers to demonstrate the reasons for the ethical and organizational impossibility of informing the individuals to be enrolled in the study, as well as the correct identification of the normative legal bases for data processing. In view of the Italian Data Protection Authority’s commitment to adopt new Deontological Rules for the processing of personal data for statistical and scientific research purposes, the aim of this contribution is to propose organic and coherent solutions, in harmony with the European data strategy.
Keywords: Personal health data; medical research; legal bases; critical issues; perspectives